Analysis of the suitability level of physics lessons with flood material - Antari, Luthfika Putri; Fauzi, Ahmad (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Padang City is one of the cities that is prone to natural disasters such as floods. The integration of physical materials with flood materials is suitable to be applied in this city. In fact, in the field, in the Physics subject package book provided by the government, there has been no integration with natural disaster materials, especially floods. To integrate flood material into Physics material, an analysis is needed first to see the suitability of Curriculum Objectives on Physics material with flood material. Methods: By using qualitative descriptive research, using the nonprobability sampling technique which is Purposive Sampling, the researchers took samples of Physics textbooks for senior high school (tenth, eleventh, twelfth grades) used by schools in the city of Padang that use the 2013 Curriculum. Findings: Based on observations of 15 high schools in the city of Padang, the 2016 revised edition of High School Physics published by Erlangga is the book studied. Based on the results of the study, the most suitable class to be inserted in this material is eleventh grade because it has the highest level of suitability. On the contrary, twelfth grade is the least suitable class to insert this material. Conclusion: To improve the relevance and effectiveness of physics learning in high school in Padang city, it is necessary to develop teaching materials that integrate flood materials, especially for eleventh grade, where the highest level of suitability is found. Novelty/Originality of this Study: This study addresses a crucial gap by incorporating natural disaster education, specifically focusing on flood-related content, into the high school physics curriculum in Padang City, an area highly susceptible to such disasters. It distinctively integrates fundamental physics principles with practical disaster mitigation knowledge, aiming to improve students' understanding and preparedness for real-world natural phenomena.